Molecular pathways involved in the control of contractile and metabolic properties of skeletal muscle fibers as potential therapeutic targets for Duchenne muscular dystrophy - Bonato, Agnese; Raparelli, Giada; Caruso, Maurizia (Frontiers in Physiology, 2024)
Duchenne muscular dystrophy (DMD) is caused by mutations in the gene encoding dystrophin, a subsarcolemmal protein whose absence results in increased susceptibility of the muscle fiber membrane to contraction-induced injury. This results in increased calcium influx, oxidative stress, and mitochondrial dysfunction, leading to chronic inflammation, myofiber degeneration, and reduced muscle regenerative capacity. Fast glycolytic muscle fibers have been shown to be more vulnerable to mechanical stress than slow oxidative fibers in both DMD patients and DMD mouse models. Therefore, remodeling skeletal muscle toward a slower, more oxidative phenotype may represent a relevant therapeutic approach to protect dystrophic muscles from deterioration and improve the effectiveness of gene and cell-based therapies. The resistance of slow, oxidative myofibers to DMD pathology is attributed, in part, to their higher expression of Utrophin; there are, however, other characteristics of slow, oxidative fibers that might contribute to their enhanced resistance to injury, including reduced contractile speed, resistance to fatigue, increased capillary density, higher mitochondrial activity, decreased cellular energy requirements. This review focuses on signaling pathways and regulatory factors whose genetic or pharmacologic modulation has been shown to ameliorate the dystrophic pathology in preclinical models of DMD while promoting skeletal muscle fiber transition towards a slower more oxidative phenotype.